Altered cytology in women treated by a Basic Work Group in Camagüey - Guillermo Medina-Fuentes (Centro Editorial Ciencias Médicas: CPICM Guantánamo, 2021)
Introduction: cervical uterine cancer is a malignant neoplasm that is associated with remarkable number of risk factors, including sexual behavior.